Genome-wide DNA methylation reveals potential epigenetic mechanism of age-dependent viral susceptibility in grass carp - Libo He; Xinyu Liang; Qian Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Immunity & Ageing, 2022)
Abstract Background Grass carp are an important farmed fish in China that are infected by many pathogens, especially grass carp reovirus (GCRV). Notably, grass carp showed age-dependent susceptibility to GCRV; that is, grass carp not older than one year were sensitive to GCRV, while those over three years old were resistant to this virus. However, the underlying mechanism remains unclear. Herein, whole genome-wide DNA methylation and gene expression variations between susceptible five-month-old (FMO) and resistant three-year-old (TYO) grass carp were investigated aiming to uncover potential epigenetic mechanisms. Results Colorimetric quantification revealed that the global methylation level in TYO fish was higher than that in FMO fish. Whole-genome bisulfite sequencing (WGBS) of the two groups revealed 6214 differentially methylated regions (DMRs) and 4052 differentially methylated genes (DMGs), with most DMRs and DMGs showing hypermethylation patterns in TYO fish. Correlation analysis revealed that DNA hypomethylation in promoter regions and DNA hypermethylation in gene body regions were associated with gene expression. Enrichment analysis revealed that promoter hypo-DMGs in TYO fish were significantly enriched in typical immune response pathways, whereas gene body hyper-DMGs in TYO fish were significantly enriched in terms related to RNA transcription, biosynthesis, and energy production. RNA-seq analysis of the corresponding samples indicated that most of the genes in the above terms were upregulated in TYO fish. Moreover, gene function analysis revealed that the two genes involved in energy metabolism displayed antiviral effects. Conclusions Collectively, these results revealed genome-wide variations in DNA methylation between grass carp of different ages. DNA methylation and gene expression variations in genes involved in immune response, biosynthesis, and energy production may contribute to age-dependent susceptibility to GCRV in grass carp. Our results provide important information for disease-resistant breeding programs for grass carp and may also benefit research on age-dependent diseases in humans.